2017
DOI: 10.5811/westjem.2016.10.32636
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Scholarship and the Emergency Medicine Educator: A Workforce Study

Abstract: IntroductionRecent literature calls for initiatives to improve the quality of education studies and support faculty in approaching educational problems in a scholarly manner. Understanding the emergency medicine (EM) educator workforce is a crucial precursor to developing policies to support educators and promote education scholarship in EM. This study aims to illuminate the current workforce model for the academic EM educator.MethodsProgram leadership at EM training programs completed an online survey consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Despite these recommendations, education scholars in EM continue to face several challenges. A recent workforce study of academic departments in EM suggested that nearly half of faculty serve in education‐related roles in most departments, yet administrative support, access to methodologic expertise, and funding for education scholarship remain scarce . Not surprisingly, prospective education scholars cite the lack of access to funding, research expertise and mentorship, and protected time as major barriers to research productivity .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these recommendations, education scholars in EM continue to face several challenges. A recent workforce study of academic departments in EM suggested that nearly half of faculty serve in education‐related roles in most departments, yet administrative support, access to methodologic expertise, and funding for education scholarship remain scarce . Not surprisingly, prospective education scholars cite the lack of access to funding, research expertise and mentorship, and protected time as major barriers to research productivity .…”
mentioning
confidence: 99%
“…CORD convened a special task force to explore education scholarship in EM. Members of this education scholarship task force in partnership with the CORD Academy for Scholarship in Education in EM recommended a systematic evaluation of factors that might enhance or impede the success of education scholars in EM . This recommendation was intended to inform future interventions aimed at strengthening the quality of scholarship within our specialty.…”
mentioning
confidence: 99%
“…This pilot study suggests that the “Step‐Back” method can be utilized to provide much needed faculty development in education research content, methodology, as well as create an opportunity for collaboration and mentorship, thereby serving to address identified needs to improve the quality and quantity of education research . Future studies should also assess what is the most effective time frame and number of group members for this technique.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a call for increased methodologic rigor in education research . An estimated 43% of academic EM faculty are primarily involved in education, but a relatively small number possess formal training or expertise in performing and disseminating education research . This problem is not unique to EM.…”
mentioning
confidence: 99%
“…In the years since the conference, our field has seen significant growth in education research training opportunities, EM specialty‐specific venues for publishing education scholarship, and prominence of EM education research leaders in national medical education arenas . The topics pursued by EM education researchers have also evolved substantially since 2012 in response to programmatic changes such as the Accreditation Council for Graduate Medical Education (ACGME) milestones project and the influences of novel modalities for education, assessment, and evaluation …”
Section: Specific Objectives Of the 2012 Academic Emergency Medicine mentioning
confidence: 99%